Symptomatic Parietal Intradiploic Encephalocele—A Case Report and Literature Review - Shi, Chen; Flores, Bruno; Fisher, Stephen; Barnett, Samuel L (Journal of Neurological Surgery Reports, 2017)
Encephalocele is a rare condition that consists of herniation of cerebral matter through openings of dura and skull. A majority of encephaloceles are congenital and manifest in childhood. We present a case of a 45-year-old man presenting with contralateral hemiparesis and found to have an extremely rare phenomenon of a symptomatic posttraumatic parietal intradiploic encephalocele (IE) manifesting 36 years following pediatric traumatic head injury. Computed tomography and magnetic resonance imaging confirmed herniation of brain tissue into the intradiploic space. Surgical treatment with reduction of the encephalocele achieved near resolution of preoperative hemiparesis on follow-up. The pathogenesis and a literature review of IE are discussed.
Keywords: parietal intradiploic encephalocele; traumatic brain injury; history; computed tomography; magnetic resonance imaging